The impact of limbus detection, arcus lipoides and limbal vessels on the primary patency of clear cornea incisions in femtosecond laser‐assisted cataract surgery. Issue 6 (27th January 2021) - Boden, Karl Thomas; Schlosser, Rosemarie; Reipen, Lena; Seitz, Berthold; Januschowski, Kai; Szurman, Peter; Wakili, Philip; Julich‐Haertel, Henrike; Rickmann, Annekatrin
Abstract: Purpose: To analyse the factors influencing the primary patency of clear corneal incisions in femtosecond laser‐assisted cataract surgery (FLACS). Methods: In this prospective single‐centre study, the graphical user interfaces of 159 patients undergoing femtosecond laser‐assisted cataract surgery were documented by video. Subsequently, the quality of limbus detection along with the incidence of vessels and an arcus lipoides were assessed by a grading system and analysed in relation to the primary patency of the incisions. In particular, the differences between a superior and a temporal main incision were analysed. Results: The designed grading system could be applied in all cases without any problems. Limbus detection was highly inhomogeneous but had no influence on the patency of the incisions (46.3% poor, 18.4% moderate, 35.1% good). The characteristics of the arcus lipoides had little influence on the patency of the main incisions. Pronounced vascular ingrowth caused more tissue bridges but did not reduce the patency of the incisions. Temporal access was generally easier to open than a superior one (97.1% versus 88.9%). Conclusion: We showed a patency rate of superior FLACS incisions of over 97% with the Femto LDV Z8 in our study. Temporal main incision is preferable to superior main incision in more difficult situations. The new grading system is suitable for further studies to provide information on the quality of the incision.